1994
DOI: 10.1007/bf02353199
|View full text |Cite
|
Sign up to set email alerts
|

Adult non-survivors: The failure to cope of victims of child abuse

Abstract: The long-term effects of child abuse have received significant attention in the research. The adult who is so affected by the trauma of child abuse is less often studied. The adult non-survivor experiences considerable and ultimately massive decompensation and failure in the ability to cope with and adjust to adult stresses. A case study is presented to illustrate this phenomenon. Issues for clinical practice and further research are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Herman et al (1989) have suggested that abuse victims may learn seductive behavior as a medium by which they tend to relate and reinforce the relationship with the perpetrator. Similarly, other clinicianresearchers Veltkamp, Miller, & Silman, 1994) have noted that individuals who experience abuse in childhood may be more likely to enter abusive situations in adulthood, resulting in poor adaptation to adult life and poor survivor skills.…”
Section: The Diagnostic and Statistical Manual Of Mental Disorders 4mentioning
confidence: 99%
“…Herman et al (1989) have suggested that abuse victims may learn seductive behavior as a medium by which they tend to relate and reinforce the relationship with the perpetrator. Similarly, other clinicianresearchers Veltkamp, Miller, & Silman, 1994) have noted that individuals who experience abuse in childhood may be more likely to enter abusive situations in adulthood, resulting in poor adaptation to adult life and poor survivor skills.…”
Section: The Diagnostic and Statistical Manual Of Mental Disorders 4mentioning
confidence: 99%
“…Returning to the self-trauma model (Briere, 1992; Briere & Runtz, 2002), simply put, child abuse can distort cognitions and alter self-capacities resulting in affect dysregulation, that is, restricted ability to regulate and control distressing emotions. Trauma Accommodation Syndrome complements this model by arguing that distorted cognition and maladaptive emotional functioning are natural consequences of persistent child abuse (Veltkamp et al, 1994). Among prisoners (K.…”
Section: Introductionmentioning
confidence: 99%